Improving Public-spending Efficiency in Czech Regions and Municipalities - Hemmings, Philip (OECD Economics Department Working Papers, 2006)
This paper looks at ways of ensuring Czech regions and municipalities are fully motivated to make efficiency improvements in public service provision and so help achieve countrywide fiscal sustainability. The very large number of small municipalities in the Czech Republic means that scale economies are difficult to exploit and the policy options for overcoming this problem are discussed. In the financing system there are issues of transparency and the balance between autonomy for the regions and municipalities and central-government power to direct resources. In terms of accountability, questions of oversight and transparency arise in the public-procurement system and benchmarking in cost and output in public services is not yet widely used. This Working Paper relates to the 2006 OECD Economic Survey of the Czech Republic (www.oecd.org/eco/surveys/Czech)